Enfrentar el consumo de sustancias psicoactivas en Nunavik: amalgama de tradiciones y de prácticas modernas - Michel Landry; Chantal Plourde; Natacha Brunelle (Drogues, santé et société, 2010)
Social-health management of psychoactive substance (PAS) users has continued to evolve along with the beliefs and discoveries regarding this new field of intervention. Thanks to our recent survey on PAS use among young Inuit, as well as a qualitative study on the Nunavimmiut’s point of view regarding PAS use in Nunavik, we can examine the situation in terms of practices designed to help people face their PAS use problem. What of the abstinence model and harm reduction strategies in the Inuit context? What do the youths, parents, leaders and elders think of the current state of addiction services in Northern Quebec? Which problem-solving strategies do the Inuit favour? We will analyze the statements collected from 109 Nunavimmiut regarding services, to help us explore the notion that strategies for providing care in the North should take into account not only cultural aspects, but also best practices. The content analysis will also enable us to describe respondents’ realities as well as their views on the present state of social‑health management of PAS users in Nunavik and on what it should be. La prise en charge sociosanitaire de l’usager de substances psychoactives (SPA) n’a cessé d’évoluer au gré des croyances et des découvertes concernant ce nouveau champ d’intervention. Une récente enquête que nous avons conduite sur l’usage de SPA des jeunes Inuits de même qu’une recherche qualitative sur le point de vue des Nunavimmiut quant à la situation de consommation au Nunavik nous permettent de poser un regard sur l’état de situation des pratiques pour aider les personnes à faire face à leur problème de consommation. Qu’en est-il du modèle de l’abstinence et des stratégies de réduction des méfaits dans le contexte inuit? Que pensent les jeunes, les parents, les leaders et les aînés de l’état actuel des services en toxicomanie dans le Nord québécois. Quelles sont les stratégies de résolution de problèmes privilégiées par les Inuits? Les propos recueillis auprès de 109 Nunavimmiut sur la question des services ...